Nationalism, Internationalization and the Dawn of the New University of The Bahamas: Looking Ahead - Davis, Linda Agatha (International Journal of Bahamian Studies, 2014)
An increasingly complex and diverse global context provides small nation states with multiple challenges. Tertiary institutions in such contexts grapple with fulfilling missions and mandates, not always of their own making, especially if they are publicly funded. This commentary poses several considerations with which the to-be-launched University of The Bahamas must contend – managing the intersection between education, societies and politics; quality assurance in higher education; knowledge production; brain drain and brain circulation; and the institution’s evolving place in the higher education landscape – as it affirms its role in the rapidly internationalizing higher education landscape. I posit that the challenge will be to (re-)align the institution’s internationalization strategies, and limited resources, with its academic mission and values, ensuring that mechanisms are established, avoiding pitfalls in what is an increasingly competitive global environment.